Digital Humanities Approach to Cultural Translation in Robert Southey’s Amadis of Gaul - Triplette, Stacey; Beshero-Bondar, Elisa; Bermúdez Sabel, Helena (My University, 2018)
This essay discusses the Amadis in Translation digital project (http:// amadis.newtfire.org), which applies TEI XML encoding to Robert Southey’s 1806 translation Amadis of Gaul, comparing it to Southey’s source, the 1547 Sevilla edition of Garci Rodríquez de Montalvo’s Amadís de Gaula. The project uses computational methods to align the source at the clause level rather than word-by-word, reflecting the radical compressions and changes Southey made to the source. The essay uses the alignment tables generated by the project to assess Southey’s use of emotion in a set of sample chapters. Contrary to what the aesthetics of the Romantic era might have led us to believe, the data show that Southey dampened the use of emotion in the source text, potentially for reasons of taste or national and cultural identity. Our digital project illustrates how computational analysis of translations can revise commonsense predictions about texts and make comparisons between translations precise and quantifiable.
Keywords: Southey; Amadis; digital humanities; TEI; Spanish; English